The role of hypoxia and radiation in developing a CTCs-like phenotype in murine osteosarcoma cells - Quartieri, Martina; Puspitasari, Anggraeini; Vitacchio, Tamara; Durante, Marco; Tinganelli, Walter (Frontiers in Cell and Developmental Biology, 2023)
Despite the improvements in cancer treatment over the past decades, tumor recurrence and metastasis are still the main concern for the success of therapy. Tumors are composed of a heterogeneous population of cells. The tumor microenvironment is not stable: it is dynamic and evolves rapidly. The blood vessels that form during tumor development exhibit a disorganized architecture, creating a hypoxic environment within the tumor. This microenvironment induces the development of a subpopulation of tumor cells with a mesenchymal phenotype, cells capable to migrating into the blood and lymphatic vessels, known as Circulating Cancer Stem Cells (CCSCs). These cells are radioresistant and are the ones that later lead to the formation of metastasis. CCSCs have markers specific to the tumor from which they originate. Moreover, they are characterized by critical markers for migration and stemness (CD133), resistance to anoikis (TrkB), which is the programmed cell death that typically occurs following cell intravasation into the bloodstream, and immune evasion (CD47). Hypoxia stimulates the stemness capacity of these cells and contributes to the selection of the subpopulation of cells that are CD133 positive. Furthermore, these CCSCs are radioresistant and further selection is possible after exposing them to radiation. Identifying these cells in circulation is challenging since they are present only in small numbers in the bloodstream. The isolation, culture, and characterization of these cells in vitro would provide the possibility to increase our knowledge of the mechanisms responsible for metastasis formation. Therefore, in this in vitro study, we selected cells with a CCSC-like phenotype using hypoxia (acute and chronic) and radiation (4 Gy X-rays) for further characterization. Our findings indicate that the combination of radiation and acute hypoxia enhances the stemness capacity of the cells, whereas chronic hypoxia imparts murine osteosarcoma cells with a phenotype resembling cancer stem-like cells (CCSCs). This phenotype is characterized by increased migration and the upregulation of CCSC markers, specifically TrkB and CD47. Our primary objective in this study is to elucidate the intricate interplay among radiation, hypoxia, and cellular responses, providing valuable insights into the complexities and prospects associated with cancer treatment.